Aplicação de polímero hidroretentor no desenvolvimento inicial de Eucalyptus grandis - Sanches, Luiz Vitor Crepaldi [UNESP] (2013)
The experiment was conducted in two stages, the first was composed by physicochemical characterization of the hydrogel in the laboratory and the second field test. Laboratory tests were performed at the UNESP - Univ Estadual Paulista, Campus of Botucatu/SP, Department of Natural Resources/Soil Science in Lageado Experimental Farm. The field test was implemented in August 2009 in Santa Clara farm (48º 40' 45 W and 23º 18' 47 S) in the city of Itatinga/SP. The polymer was studied Hydrosolo H ™ capable of retaining 500 ml of water per gram of polymer. The field experiment adopted the experimental design factorial 2 x 5 (2 modes of application and 5 polymer doses plus the control) in a randomized block design with four replications, plots with 49 plants, being 25 useful to analyse. The applications of hydrogel were performed on furrow and surface simulating the use with of the planter, and applicator with showerhead type, being used the quantities of polymer 0; 0,85; 1,50; 2,20; 2,90 and 3,60 g.plant-1. In laboratory was evaluated density, water holding capacity, pH and electrical conductivity of the hydrogel, and the experimental field were evaluated plant height, stem diameter relative chlorophyll index, and number of branches at planting, 15 and 30 days after transplantation. The survival rate, volume of water used in each treatment, number of irrigations needed, interval days between irrigations and operating costs and the polymer were measured after experiment. The polymer promoted great cost x benefit, because it occurred 100% survival of plants after 30 days of transplantation; reduced by 57% the number of irrigations needed to promote forest stand; increased the interval between irrigations, from 4 for 10 days; significant reduced in water consumption in irrigation both as per hectare or per plants, occurring savings of 58% (18,3 m3 ha-1), the operating cost of irrigation ...